Crystal Structure of (3)-3 3-Dihydro 2H-Indol - Hökelek, T.; Erçaǧ, A.; Çorch, U.; Vázquez Lõpez, E.M.; Üstün Özgür, M.Ü. (Japan Society for Analytical Chemistry, 2005)
In the title compound, C16H14N2O2, the dihedral angles between pyrrole and benzene rings are 1.66(9) and 83.25(8)°. Intermolecular N-H·N and C-H·O hydrogen bonds stabilize the crystal structure by causing the formation of a supramolecular architecture. It belongs to the space group P21/c with cell parameters a = 10.220(3), b = 13.812(4), c = 10.420(3)Å, β = 110.771(4)°. 2005 © The Japan Society for Analytical Chemistry.